The use of Economic means in Libya's Foreign Policv in Africa: 1970 — 1974 - SHEMBESH, ALI (Dirasat in Economics and Business, 1978)
Forein Plicy is a continuous process, requiring constant studv and reinterpretation of changing situations to achieve certain national goals. Foreign policv can, therefore, be defined in terms of an ends-means relation-shin. Foreign policy is the relation between input ( means ) and output ( ends ). In order for a state to achieve certain goals in the international arena, it has to have certain means. By the same token, a state has to have specific foreign policv objectives in order to use those available means in the best possible manner.